New Methods to Improve Large-Scale Microscopy Image Analysis with Prior Knowledge and Uncertainty - Stegmaier, Johannes (KIT Scientific Publishing, 2021)
Multidimensional imaging techniques provide powerful ways to examine various kinds of scientific questions. The routinely produced data sets in the terabyte-range, however, can hardly be analyzed manually and require an extensive use of automated image analysis. The present work introduces a new concept for the estimation and propagation of uncertainty involved in image analysis operators and new segmentation algorithms that are suitable for terabyte-scale analyses of 3D+t microscopy images.